A Risk Analysis of Sugarcane Farming (Case Study in Subang, West Java) - Muhammad Irfani Abdullah; Sri Lestari; Yusmi Nur Wakhidati; Irene Kartika Eka Wijayanti; Altri Mulyani (Universitas Djuanda, 2026)
Sugarce farming in Indonesia has been facing the problems of lack of raw material and low processing yield. Sugarcane farming carried out by farmers has been facing several risks. This research aims to analyze risk management by sugar cane farmers. The risk management process is carried out in a sequence : 1) risk identification, 2) risk assessment, 3) identification of risk mitigation. Risk identification stage has found 13 risks that is devided into 3 groups : 1) nature related risks, 2) production resource related risks, 3) economic factor related risks. Based on risk assessment there are five high grade risks, seven medium grade risks and one low grade risks. It is noted that there are 20 risk mitigations carried out by farmers. Boktor and burned cane have highest risk scores. Drought is one of some risks that has high score. Sugar mill company as farmers’ partner can be involved in risk mitigation by adding pond capacity and the number of pumps and irrigation pipes.